2021
DOI: 10.1177/2374373521996951
|View full text |Cite
|
Sign up to set email alerts
|

Dignity Therapy for End-of-Life Care Patients: A Literature Review

Abstract: Dignity therapy as an intervention has been used for individuals receiving palliative care. The goal of this review is to explore the current state of empirical support to its use for end-of-life care patients. Data sources were articles extracted from search engines PubMed, Cochrane, Embase, CINAHL, Web of Science, and PsycINFO. The years searched were 2009 to 2019 (10-year period). The review process was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results revealed the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…As in previous studies on this issue, our results highlight the positive effects of palliative care, through specialized support networks at home. In this sense, the support of palliative care teams has proved to be essential to alleviating feelings of anguish, depression and caregiver burden and other needs inherent to care [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies on this issue, our results highlight the positive effects of palliative care, through specialized support networks at home. In this sense, the support of palliative care teams has proved to be essential to alleviating feelings of anguish, depression and caregiver burden and other needs inherent to care [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, there has been a growing number of papers regarding DT concerning psychosocial and spiritual outcomes for people with palliative care needs. Studies have found various benefits, such as decreased anxiety and depression and an improved sense of dignity, meaning and purpose among people approaching the end of their life 1–17▪,18–23▪,24 . DT is a well-accepted, tested and effective intervention; nevertheless, there needs to be a clear cultural understanding of the effectiveness of DT, particularly since it was developed and tested in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…This may affect its acceptance and implementation in other countries and cultures. Cultural competence in palliative care is key to delivering dignified and personalised care for individuals with diverse beliefs, values and needs 22,23▪–26 . Understanding the importance of cultural competence is also essential to healthcare policy and training of healthcare professionals across the international spectrum 22,23▪–26 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations